Beneficial roles of the AhR ligand FICZ on the regenerative potentials of BMSCs and primed cartilage templates. Issue 18 (13th April 2022) - Huang, Jing; Wang, Yining; Zhou, Yi
Abstract : FICZ/AhR axis might be a potential target to achieve optimal bone regeneration for both BMSCs and primed cartilage templates. Abstract : Bone marrow-derived mesenchymal stem cells (BMSCs) are commonly used seed cells, and BMSC-derived primed cartilage templates have been shown to achieve bone regeneration in bone tissue engineering. Aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor involved in various cellular processes such as osteogenesis and immune regulation. This study investigated the effects of the AhR endogenous ligand 6-formyl (3, 2- b ) carbazole (FICZ) on the behavior of BMSCs and cartilage templates as well as the possible underlying molecular mechanisms. AhR expressions in rat bone marrow and isolated BMSCs were detected via immunohistochemistry (IHC) and immunofluorescent staining. Alkaline phosphatase staining and alizarin red staining showed that FICZ treatment enhanced the osteogenic potential of BMSCs without influencing their proliferation. FICZ was shown to alleviate the LPS-induced inflammatory cytokines IL-1β, 6 and TNF-α via the quantitative polymerase chain reaction (qPCR). In the chondrogenic process from BMSCs to primed cartilage templates, the expressions of AhR and its target gene cytochrome P450 subfamily B member 1 (CYP1B1) were inhibited. However, IHC staining demonstrated that AhR was still involved in the subcutaneous ossification of cartilage templates. Then, the effects of FICZ on cartilage templates were investigated. The osteogenic markers were upregulated by FICZ administration. The RAW 264.7 treated by condition medium of FICZ-treated cartilage templates exhibited an anti-inflammatory phenotype. Finally, high-throughput sequencing was applied to analyze the differentially expressed genes (DEGs) in the FICZ-treated cartilage templates. The upregulation of cytochrome P450 subfamily A member 1 (CYP1A1) and sphingomyelin phosphodiesterase 3 (Smpd3) were verified by qPCR, which might be the downstream targets of AhR in the cartilage templates promoting osteogenesis and macrophage polarization. These data implied a beneficial role of FICZ in the regenerative potentials of both BMSCs and primed cartilage templates. The FICZ/AhR axis might be a practical target to achieve optimal bone regeneration.